ANALISIS PENGEMBANGAN KANTOR PELAYANAN, PENYULUHAN DAN KONSULTASI PERPAJAKAN (KP2KP) MENJADI KANTOR PELAYANAN PAJAK (KPP) PRATAMA DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK (Studi pada Kantor Pelayanan, Penyuluhan dan Konsultasi Perpajakan Kabupaten Sumenep - Putri, Nani Kardina (Jurnal Mahasiswa Perpajakan, 2015)
Sumenep Regency applies Services, Counseling and Taxation Consultation Office system, while in Pamekasan Regency applies Taxation Services Office system. This study are aimed to describe the internal and external factors that support the development of services, counseling and taxation consultation office of Sumenep Regency into the Pratama taxation services office to increase tax compliance. The study used qualitative method with descriptive research. In addition, used data reduction, data presentation and inference methods are used in order to analyze the data. The study focused on the internal factor, such as human resources, behavioral / managerial decisions, and organizational structure, and the external factor, such as demographic characteristics, technology development and market changes that affect the development ofÂ  Services, Counseling and Taxation Consultation Office of Sumenep Regency into the Pratama Taxation Services Office to increase tax compliance. This development is analyzed based on direct money cost and time cost. This study found that both internal and external factor can support the development ofÂ  Services, Counseling and Taxation Consultation Office into the Pratama Taxation Services Office. Then, it can be concluded that if Sumenep Regency applies the Pratama Taxation System, the tax compliance will increase. Keywords : Development Of Services, Counseling, Taxation Consultation